Dietary and lifestyle patterns in relation to high blood pressure in children. Issue 6 (June 2015) - Farajian, Paul; Panagiotakos, Demosthenes B.; Risvas, Grigoris; Micha, Renata; Tsioufis, Constantinos; Zampelas, Antonis
<x xml:space="preserve">Abstract</x> Objective: The objective of the present study was to investigate possible associations of dietary patterns with high blood pressure (BP) in a nationwide cross-sectional sample of 10–12 years old Greek schoolchildren. Methods: Anthropometric measurements and information on dietary (by a semi-quantitative food frequency questionnaire) and physical activity habits were obtained from the children. BPs was measured in a single occasion using a standard protocol. Data from 2024 normal energy reporting children were included in the analysis. Principal component analysis was applied to identify dietary patterns. Results: Seven dietary components (patterns) were extracted explaining 55% of the total variation in intake. Multiple logistic regression analysis revealed that predictors of high BP (75th percentile of SBP and/or DBP) were a pattern mainly characterized by the high consumption of cheese and red processed meat [odds ratio (OR) 1.15; 95% confidence intervals (CI) 1.03–1.30], being overweight (OR 2.10; 95% CI 1.61–2.73) or obese (OR 3.84; 95% CI 2.44–6.06) and breakfast frequency (OR 0.95; 95% CI 0.90–0.99). After controlling for sodium intake levels, the dietary pattern did not remain a significant predictor of high BP, indicating the potential mediating effect of sodium in the association. Conclusion: A dietary pattern that is characterized by high cheese and red processed meat consumption increases the likelihood of having high BP in children, probably through increasing dietary sodium intake. These findings could guide future interventions or public health initiatives to prevent the increasing rates of childhood elevated BP levels.